El Juez Constitucional y el llamado nuevo Derecho - Ociel Castaño, Luis (2023)
This article shows some changes that have occurred in the way domestic law was understood in the field of public law and, especially, of constitutional law. Based on the tenets of neoconstitutionalism, the author emphasizes the role of modern constitutional courts in creating law, and the rupture Colombian case law has experienced since 1992.